Effect of surface flux boundary conditions on transient suction distribution in homogeneous slope - Yunusa, Gambo Haruna (2015)
Rainfall-induced slope failure is a common natural disaster that occurs frequently in many parts of the world. Many studies have been conducted on the effect of advancement of wetting front on reduction or elimination of the additional shear strength provided by matric suction in unsaturated soil. However, the inclusion of boundary flux condition such as evaporation in predicting soil suction for rainfall-induced slope failure analyses is still limited. Therefore, this study investigate the combined effect of two boundary flux (infiltration and evaporation) on transient suction distribution and hence the factor of safety (FOS) of a modelled slope which consist of slope height and horizontal distance of 5 and 47 m respectively with a slope angle of 21°. One year rainfall and evaporation data of a site in Johor Bahru, Malaysia were collected for the study and two months were selected to represent the wet and dry seasons based on the two predominant wind systems which brings rainfall in Malaysia (Northeast and Southwest monsoons). Soil samples were collected from the site for laboratory testing and the relevant soil properties required in the analyses were obtained. Initial soil condition was determined from Soil Water Characteristics Curve (SWCC) of the soil sample from the study area and these initial conditions were simulated at the beginning of each analysis to enable realistic condition of the soil to be obtained. The seepage analyses were conducted with Seep/w and the pore water pressure determined from the seepage analyses were used as input parameters in the slope stability analyses carried out with slope/w. The results of the analyses show that considering flux boundary condition has a great influence in maintaining negative pore water pressure in unsaturated soil especially during wet period when there is more water infiltrating the soil. Moreover, inclusion of evaporation in seepage analyses give more realistic pore water pressure and hence better prediction of FOS of the slope.